Exploring an EFL Teacher’s Translanguaging Practice of Giving Instruction in English Learning and Teaching Process: A Case Study at Junior High School in Bogor - Saqinah, Amanda; Samsi, Yogi Setia; Utami, Praditya Putri (FKIP - Universitas Riau, 2025)
This study explores how an English as a Foreign Language (EFL) teacher implements translanguaging practices when giving instructions in a multilingual junior high school classroom in Bogor, Indonesia. Using a qualitative case study approach, data were collected through classroom observations, interviews, and documentation. The findings reveal that the teacher spontaneously employed translanguaging strategies to facilitate comprehension, reduce confusion, and enhance student engagement. Three types of translanguaging were identified: intrasentential, intersentential, and tag-switching. Intrasentential and intersentential translanguaging were most frequently used to scaffold instructions and explain tasks, while tag-switching was used to manage classroom interaction and attention. Although not formally planned in the lesson plan, the use of translanguaging emerged as a purposeful pedagogical strategy to support students’ understanding and participation. This study underscores the importance of recognizing translanguaging as an inclusive and effective instructional tool in multilingual EFL classrooms.